그래프 결합면체 위에 있는 정규스몰커버의 베티넘버들 - 박상건 (The Graduate School, Ajou University, 2014)
In this thesis, we compute the i-th a-numbers for the Petersen graph and Furry graphs. We, therefore, compute the i-th Betti number of the canonical small cover over graph associahedron P_{B(G)}, where G is the Petersen graph or Furry graphs.
학위논문(석사)--아주대학교 일반대학원 :수학과,2014. 8
Keywords: 그래프결합면체